Biological survey of the Prince Edward Islands, December 2008 - Cooper, J.; Bester, M.N.; Chown, S.L.; Crawford, R.J.M.; Daly, R.; Heyns, E.; Lamont, T.; Ryan, P.G.; Shaw, J.D. (South African Journal of Science, 2010)
A biological survey of the Prince Edward Islands took place in December 2008. The survey repeated an earlier survey of the populations of surface-nesting seabirds on both islands and of fur seals (Arctocephalus spp.) and alien plants on Prince Edward Island in December 2001. Observations on burrowing seabirds, macro-invertebrates and plant communities on Prince Edward Island and an oceanographic survey of surrounding waters were also included. The survey confirmed many of the observations made on the earlier survey and permitted an assessment of trends in the abundance and distribution of biota since 2001.